2019
DOI: 10.1007/s40520-019-01238-y
|View full text |Cite
|
Sign up to set email alerts
|

Ageing-friendly cities for assessing older adults’ decline: IoT-based system for continuous monitoring of frailty risks using smart city infrastructure

Abstract: Background and aims Population ageing is a typical phenomenon of developed countries with a great influence in their economy and society, with an increment on age-related expenditures. Disruptive solutions are needed to deploy new costeffective and sustainable solutions for aging well and independent living of our seniors. In this sense, new technological paradigms as IoT technologies and smart cities have the potential to become main drivers for innovation uptake. The purpose of this study is to describe a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The design and implementation of evidence-based practice, such as the use of ICT for managing frailty depend on successful behavioral change interventions [49]. Surprisingly, only one study has explicitly used behavioral changes, which were measured using outdoor walking distances and weekly visiting patterns as outcome variables [40]; more importantly, none of the studies identified in this literature review used a theoretical approach regarding behavioral change. One of these frameworks is the well-known 'COM-B' system.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The design and implementation of evidence-based practice, such as the use of ICT for managing frailty depend on successful behavioral change interventions [49]. Surprisingly, only one study has explicitly used behavioral changes, which were measured using outdoor walking distances and weekly visiting patterns as outcome variables [40]; more importantly, none of the studies identified in this literature review used a theoretical approach regarding behavioral change. One of these frameworks is the well-known 'COM-B' system.…”
Section: Discussionmentioning
confidence: 98%
“…Most of the studies in this group were descriptive. As in the frailty detection group studies, some studies asserted that the ICT employed could be used for screening and preventing frailty; however, no quantitative data were provided [5,[36][37], whereas other studies were found to monitor the evolution of the monitored variables (e.g., subject activity and frailty status, [38][39][40][41][42]) effectively.…”
Section: Technology Readiness Level Of the Ict Used To Manage Frailty In Older Adultsmentioning
confidence: 99%
“…IoT health systems allow doctors to monitor patients constantly and to suggest corrective actions according to the analyzed data [29,37,38]. For example, one of the goals of City-4Age and ACTIVAGE H2020 projects is the assessment of frailty using IoT technology based on rules [39]. Furthermore, there are a few efforts to apply microservices in the health domain.…”
Section: Related Workmentioning
confidence: 99%
“…IoT services are used for early detection and prevention of cognitive performance decrease and in the cases of falling of the elderly [11]. It is becoming a new platform of assessment of the housing environment, It is important mainly for the personalization of health and care services as well as for prevention [1]. The basic indicators of daily activity, whose monitoring is used in IoT in the housing microenvironment are as follows: number of steps, distance covered, and walking average speed, type of POI (points of interest), number of visit per POI, visit duration, number of trips, used bus lines, distance, and time per trip [1].…”
Section: Promoting Independence In Housing Environment Availability mentioning
confidence: 99%